INTANGIBLE ASSETS: ISSUES OF ACCOUNTING AND MANAGEMENT IN THE CONTEXT OF DIGITALIZATION OF THE ECONOMY - D. V. Voyko; A. V. Voyko (Вестник университета)
The issues of classification and approaches to management of intangible assets of companies have been considered. Main features of intangible assets have been examined, as well as normative regulation of financial accounting of them. The important point of intangible assets management is their classification and distribution to homogeneous groups, that allows us create and clarify intangibles’ management policy in terms of digitalization. In addition, the authors have paid attention in the article to the issues of intangible assets valuation. Basic stages of intangible`s assessment have been analyzed, as well as current problems of estimation of true value of intangible assets.